"Big Brother's Bigger Brother": The Visual Politics of (Counter) Surveillance in Baltimore. Issue 4 (28th August 2020) - Snyder, Benjamin H.
Abstract : In 2016, without the knowledge of its citizens, Baltimore City Police deployed a military aerial surveillance technology called Wide Area Motion Imagery (WAMI), which can track the movements of every person in public view over the entire city. Though the trial of the "spy plane, " as the program was dubbed, quickly ended in scandal, organizers from Baltimore's low‐income minority neighborhoods successfully rebooted the program in 2020, this time framing WAMI partly as a tool of "sousveillance" (watching "from below") that can track the movements of police officers. The paper shows how organizers "rebranded" WAMI around two conceptions of sousveillance—"citizen‐centered" and "state‐centered"—creating an unlikely coalition of supporters from both pro‐ and anti‐policing sides of the criminal justice reform debate. But while the renewed program has vowed to be a "Big Brother" to the state, it will continue to be used for traditional surveillance, raising troubling questions about privacy. The article sheds light on the politics of watching and being watched in the era of technology‐driven criminal justice reform.